2016
DOI: 10.1001/journalofethics.2016.18.6.msoc2-1606
|View full text |Cite
|
Sign up to set email alerts
|

Ethical and Epidemiological Dimensions of Labeling Psychosis Risk

Abstract: The past two decades have marked an increase in research on the prodromal stages of schizophrenia that precede a first episode of psychosis. Criteria for a clinical high risk (CHR) state for psychosis have been validated and included in the DSM-5 as the attenuated psychosis syndrome and as requiring further study. This was hotly debated, given the concern of stigmatizing young people who would receive this psychosis risk label. In this article, I review ethical issues related to the psychosis risk label, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Oftentimes, significant delays in the initiation of adequate treatment contribute to poor outcome (Penttilä et al 2014 ), which are fostered by stigmatising, negative attitudes both towards people with mental illness and towards help-seeking for mental problems (Schnyder et al 2017 ). Stigma against people with mental illness, in turn, is primarily fuelled by illness-associated unusual behaviours that, in particular in case of psychoses, are perceived by others as unpredictable and dangerous (Corcoran, 2016 ; Imhoff, 2016 ). Thus, a comprehensive early detection of and intervention in persons at increased risk for developing a psychotic disorder may not only improve outcomes and reduce costs (Fusar-Poli et al 2013 ) but may also reduce stigmatization by avoiding overt psychotic symptoms and the label ‘schizophrenia’, and by providing adequate education early on (Corcoran, 2016 ; Imhoff, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oftentimes, significant delays in the initiation of adequate treatment contribute to poor outcome (Penttilä et al 2014 ), which are fostered by stigmatising, negative attitudes both towards people with mental illness and towards help-seeking for mental problems (Schnyder et al 2017 ). Stigma against people with mental illness, in turn, is primarily fuelled by illness-associated unusual behaviours that, in particular in case of psychoses, are perceived by others as unpredictable and dangerous (Corcoran, 2016 ; Imhoff, 2016 ). Thus, a comprehensive early detection of and intervention in persons at increased risk for developing a psychotic disorder may not only improve outcomes and reduce costs (Fusar-Poli et al 2013 ) but may also reduce stigmatization by avoiding overt psychotic symptoms and the label ‘schizophrenia’, and by providing adequate education early on (Corcoran, 2016 ; Imhoff, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stigma against people with mental illness, in turn, is primarily fuelled by illness-associated unusual behaviours that, in particular in case of psychoses, are perceived by others as unpredictable and dangerous (Corcoran, 2016 ; Imhoff, 2016 ). Thus, a comprehensive early detection of and intervention in persons at increased risk for developing a psychotic disorder may not only improve outcomes and reduce costs (Fusar-Poli et al 2013 ) but may also reduce stigmatization by avoiding overt psychotic symptoms and the label ‘schizophrenia’, and by providing adequate education early on (Corcoran, 2016 ; Imhoff, 2016 ). Yet, as only few persons with a beginning psychosis seek help in their prodromal phase (Schultze-Lutter et al 2015 a ; Kazdin, 2017 ), a comprehensive preventive approach would require assertive community programs, incl.…”
Section: Introductionmentioning
confidence: 99%
“…The Preceded information ascertained that stigma associated with mental illness have many ethical implications in the context of Responsible Conduct of research (RCR). These ethical implications can be seen in the form of issues related to consent form (Fisher & Oransky, 2008;Vaz & Srinivasan, 2014), fair treatment and good respect for individual rights concerning treatment choices (Carrier, Banayan, Boley, & Karnik, 2017;Corcoran, 2016), use of various forms of treatments, participation in the clinical studies at the national level and issue of possible use of data for national or governmental purpose (Alahmad, Al-Jumah, & Dierickx, 2012;Ayalon, Karkabi, Bleichman, Fleischmann, & Goldfracht, 2015;Campbell et al, 2015;Sharma et al, 2013;Vaz & Srinivasan, 2014). Indeed, scientific researchers and those who are conducting research studies about mental health in the primary health care settings (Dubois et al, 2011); must consider the applications of ethical standards as suggested by RCR with cautions.…”
Section: Implications Of Mental Illness Stigma For Research and Ethicsmentioning
confidence: 99%
“…Researchers should follow rules concerning use of consent forms and how it might vary according to the target population being studied, the setting or cultural context where the study taking place (Alahmad et al, 2012;Carrier et al, 2017;Chowdhury, 2016;Corcoran, 2016;Mittal, Dean, Mittal, & Saks, 2015;Pires Marques, 2017;Sharma et al, 2013;Shen et al, 2017;Vaz & Srinivasan, 2014). Literature noted different components for consent forms, however they all point to the one important piece of "providing enough and detailed information in order to get the consent".…”
Section: Implications Of Mental Illness Stigma For Research and Ethicsmentioning
confidence: 99%
“…A second argument against including APS in the DSM-5 is that a diagnosis of APS would expose young people to internal and external stigmatization (Corcoran, First, & Cornblatt, 2010;Yang, Wonpat-Borja, Opler, & Corcoran, 2010), which may be especially problematic because the majority of people identified as at risk do not later convert to full psychosis in longitudinal studies (Addington & Heinssen, 2012;Fusar-Poli et al, 2013). This raises interesting ethical considerations, as an interest in avoiding the potential stigmatization associated with labelling someone as "at-risk of psychosis" may result in a threat to autonomy by providing the person with incomplete information regarding the underlying factors of his or her presenting problems (Corcoran, 2017). Although research has demonstrated that at-risk individuals do not appear to perceive much stigma associated with the labels "ultra-high risk" and "attenuated psychosis syndrome," (at least not to the degree that clinicians perceive this stigma on behalf of these individuals; Kim et al, 2017), research is scant as to how peers around the modal age of APS development perceive those in the high risk state.…”
mentioning
confidence: 99%